Negative-bias temperature instability – insight from recent dynamic stress experiments - Ang, Diing Shenp (2013)
The purpose of this paper is to summarize key experimental evidences on the important role of hole trapping on negative-bias temperature instability (NBTI). For a long time, the focus of this research topic had been on interface degradation driven by hydrogen transport and hole trapping was regarded as a side effect arising out of fast measurement techniques proposed to mitigate the effect of recovery on measurement data. In recent studies, we showed that the threshold voltage (Vt) fluctuations one typically observed under dynamic NBTI were mainly the result of hole trapping and not hydrogen-transport driven interface-state generation/passivation proposed earlier. In particular, the cyclical Vt shifts and constant Vt recovery are inconsistent with the basic principle of the hydrogen transport model. Such behaviors are better described in terms of hole trapping/detrapping at pre-existing oxide defects. We have also shown that interface degradation during NBTI stressing has no apparent impact on bulk (oxide) trap generation, i.e. interface trap generation does not lead to bulk trap generation. This result raises further questions on the validity of the hydrogen transport mechanism and the long standing hypothesis on hydrogen-induced bulk trap generation and gate oxide breakdown. Finally, it is shown that the transient hole trapping responsible for the Vt shift fluctuations could be transformed into more permanent trapped holes under NBTI stressing. The extent of transformation is accelerated by a high oxide field and temperature. An excellent correlation with stress induced leakage current indicates that such transformation underlie the generation of bulk traps reported by earlier studies.